2015
DOI: 10.1111/rda.12627
|View full text |Cite
|
Sign up to set email alerts
|

Coenzyme Q10 and α‐Tocopherol Prevent the Lipid Peroxidation of Cooled Equine Semen

Abstract: Biotechnology applied for equine semen increases the levels of reactive oxygen species and reduces the natural antioxidant defence, by both dilution and removal of seminal plasma. Therefore, the aims of this study were to evaluate the effect of adding coenzyme Q10 (CoQ10) and α-tocopherol (α-TOH) to the cooling extender, singly or in combination, on sperm parameters, and their effectiveness in preventing lipid peroxidation (LPO) of equine semen during cooling at 5°C for 72 h. Ten adult stallions of proven fert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 39 publications
(82 reference statements)
2
9
1
Order By: Relevance
“…By preventing the oxidation of lipids in spermatozoal membranes, the integrity of the plasma membrane is maintained, and the spermatozoa survive. Similarly, previous studies in humans [28,29], bulls [30], and horses [19,31,32] have shown that CoQ10 acts as an excellent tool in repairing damage to the spermatozoal plasma membrane.…”
Section: Resultssupporting
confidence: 61%
“…By preventing the oxidation of lipids in spermatozoal membranes, the integrity of the plasma membrane is maintained, and the spermatozoa survive. Similarly, previous studies in humans [28,29], bulls [30], and horses [19,31,32] have shown that CoQ10 acts as an excellent tool in repairing damage to the spermatozoal plasma membrane.…”
Section: Resultssupporting
confidence: 61%
“…Our results are in contrast with those obtain by Yousefian et al (2014) and Nogueira et al (2015). Our difference value measured at 48 h (Figure 4) between CRT and CRT þ Q for motility can be explained with a possible negative effect due to the high amount of antioxidant used.…”
Section: Discussioncontrasting
confidence: 99%
“…Previous studies have shown that the addition of the antioxidant α-tocopherol to semen extender may improve cryopreservation or cooling of stallion semen [2,29]; this antioxidant avoids the peroxidation of lipids in the plasma membrane, thus contributing to sperm preservation [30]. Gums provide protection against cold shock because of their physicochemical characteristics since they can retard or minimize the following processes: crystallization of water or sugar; gravitational sedimentation of suspended particles; loss of small molecules or ions due to the formation of an impermeable film; and syneresis in the gels, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…The solvent was evaporated in a rotavapor at 35 °C, followed by the lyophilization process. The concentration of α-tocopherol in the experimental group TOC (10%) was chosen from previous studies [2].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation